The Impact of Financial Management Reforms on Budget Efficiency, Transparency, and Wastage Reduction Across Diverse Regions - Rashied, Ahmed Saeed; Chyad, Azzam Khalid; Qasem, Wadah; Abbas, Nazar Habeeb (Journal of Ecohumanism, 2024)
Background: Financial management reforms are vital for enhancing public sector efficiency, transparency, and accountability. These reforms aim to optimize budget allocation, reduce fiscal wastage, and improve governance. Objective: This study evaluates the impact of financial management reforms implemented across public sector institutions in five global regions between 2015 and 2023. Key performance indicators assessed include budget efficiency, financial transparency, and wastage reduction. Methods: A mixed-methods approach was utilized, incorporating quantitative analysis of financial data from 60 public sector institutions across five regions. A total of 180 financial reports were reviewed alongside 30 qualitative interviews with key stakeholders such as finance officers and policymakers. The study employed regression analysis, Difference-in-Differences (DiD), and thematic coding to analyze the impact of the reforms. Results: The results revealed a 19.3% improvement in budget efficiency, with transparency scores increasing by 25%. Wastage across key sectors such as health and infrastructure was reduced by over 50%, particularly in regions like Sub-Saharan Africa and South Asia. Conclusion: Financial management reforms significantly improved fiscal performance, transparency, and wastage reduction in public sector institutions. However, the success of these reforms depends heavily on institutional capacity and political will, emphasizing the need for continuous support and capacity-building initiatives to sustain progress.